The Effects of Country of Origin and Country of Service Delivery on Students’ Attitude Towards Foreign University - Chiu, Mei Chee (2014)
Internationalization of higher education leads to the interest of examining the effect of country of origin on students’ perception of university since study abroad and establishment of international branch campus in different countries are becoming a choice for students to further their higher education. Due to the growing of demand of higher education, it is important to understand students’ attitude toward university and what makes the university attractive to them. Therefore, in order to maintain the university performance and compete in the international market, it is important to develop and maintain a certain level of brand equity by creating and adding value to the university brand. In addition, the competition between the international universities also raises the curiosity of knowing whether the country of origin and country of service delivery would influence students’ attitude towards the university. This research studies the effect of country of origin and country of service delivery on prospective students’ attitude towards university. Prospective students’ attitudes toward university were measured by using multiple variables namely university image, university reputation, brand credibility, perceived quality and brand equity. Furthermore, this study also aims at identifying the relationships between the variables and their impacts on brand equity. Factorial design was employed by using stimuli material: two universities from UK and India and their branch campus in Malaysia. Quantitative method was used to collect data through questionnaires. Four questionnaire featuring four campuses were developed. Survey was conducted with 260 respondents in Klang Valley, Malaysia. Relationships were found between the independent variables. There is a positive impact of university reputation on brand credibility, perceived quality and university image. Furthermore, perceived quality was found to have the most impact on university brand equity. The effect of country of origin and country of service delivery was also studied to determine whether it plays a role in affecting prospective students’ attitude toward the university. The result revealed that country of origin play a more important role than country of service delivery on students’ perception in terms of brand equity, perceived quality, university image, brand credibility and university reputation. Following these findings, detailed discussion and managerial implications were provided. This study supported previous studies findings and provided extension to the study of brand equity in higher education by including the effect of country of origin. For university management, the impact of various factors influencing brand equity provides direction on which sector should they focus their marketing efforts on. However, this study involves only respondents from limited geographical area in Malaysia which limit the result generalizability. Additionally, the proposed framework does not take into consideration factors that moderate the influence of related variables on brand equity. Recommendations for future research were discussed. Most importantly, this study makes a significant contribution into the existing literature by examining the role of country of origin and country of service delivery effect in students’ attitude towards the university which is measured using brand equity, perceived quality, university image, brand credibility and university reputation.